Decoding four-finger proprioceptive and tactile stimuli from magnetoencephalography - Nyländen, Paavo (2024)
This study aimed to investigate the feasibility of decoding proprioceptive and tactile stimuli applied to the fingers using magnetoencephalography (MEG) signals and support vector machines (SVMs). With the advancement of neuroprosthetic brain-computer interfaces (BCIs) there is a growing need to enhance the control of these devices by accurately decoding subtle sensory stimuli. This research focuses on the temporal dynamics of MEG responses to such stimuli, investigating their potential to inform the development of more dexterous and responsive neuroprostheses.